Digital Literacy Practices and Identity Negotiation among Thai Students in Indonesian EFL Classrooms: Advancing SDG 4 through Quality and Inclusive Education - Lestari Budianto; Slamet Setiawan; Pratiwi Retnaningdyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To investigate how Thai students in Indonesia negotiate their identities through digital literacy practices in an English as a Foreign Language (EFL) classroom, contributing to Sustainable Development Goal 4 (SDG 4) by examining how digital practices support quality and inclusive education in multilingual higher education contexts. Method: Employing a qualitative approach, the study involved three Thai students from the English Education Department at Universitas K.H. Abdul Chalim. Data were collected through classroom observations and self-administered interviews and analyzed using thematic analysis. Result: The findings indicate that digital literacy practices facilitated language learning, classroom participation, and identity negotiation as international EFL learners. The participants utilized digital tools, including translation applications, social media, online learning platforms, and artificial intelligence tools, to adapt to academic and sociocultural environments. Their identity construction was shaped by cross-cultural experiences, multilingual communication, and digital engagement within the EFL classroom. Novelty: The study contributes to the growing literature by demonstrating the interconnected role of digital literacy and identity construction among international students in higher education EFL contexts. It also provides novel insights from the underexplored context of Thai students studying in Indonesia, highlighting how digital literacy practices support both academic adaptation and identity development.